Dusp6 immunohistochemistry is associated with the response of atypical endometrial hyperplasia and early endometrial cancer to conservative treatment. Issue 3 (9th December 2021) - Travaglino, Antonio; Raffone, Antonio; Gencarelli, Annarita; Micheli, Mariacarolina; Franco, Laura; Zullo, Fulvio; Mollo, Antonio; Di Spiezio Sardo, Attilio; Bifulco, Giuseppe; Insabato, Luigi
Abstract: Objective: Dual‐specificity phosphatase 6 (Dusp6) was proposed as a predictive marker of response of atypical endometrial hyperplasia (AEH) and early endometrial cancer (EEC) to conservative treatment. However, its predictive accuracy has never been calculated. We aimed to define it in conservatively treated AEH and EEC. Methods: All patients <45 years with AEH or EEC and conservatively treated with hysteroscopic resection + LNG‐IUD insertion from 2007 to 2018 were retrospectively assessed. Dusp6 immunohistochemical expression was assessed and dichotomized as "strong" vs "weak". Relative risk (RR) for "no regression" and "recurrence" or AEH/EEC was calculated. Predictive accuracy was calculated as sensitivity, specificity, positive and negative predictive values (PPV, NPV) and area under the curve (AUC) on receiver operating characteristic curve. Results: Thirty‐six women were included. Weak Dusp6 immunohistochemical expression was significantly associated with increased risk of resistance to treatment, with a RR = 16 ( P  = 0.0074); predictive accuracy analysis showed sensitivity = 80%, specificity = 90%, PPV = 57.1%, NPV = 96.4%, AUC = 0.85. A weak Dusp6 expression was not significantly associated with the risk of recurrence after an initial regression (RR = 0.4; P  = 0.53). Conclusion: Weak Dusp6 expression appears as a significant predictor of resistance of AEH/EEC to fertility‐sparing treatment, with moderate predictive accuracy. Weak Dusp6 expression is significantly associated with resistance of atypical endometrial hyperplasia or early endometrial cancer to fertility‐sparing treatment, with moderate predictive accuracy. Abstract : Weak Dusp6 expression is significantly associated with resistance of atypical endometrial hyperplasia or early endometrial cancer to fertility‐sparing treatment, with moderate predictive accuracy.